Painting the diversity of a world's favorite fruit: A next generation catalog of cultivated bananas - Sardos, Julie; Cenci, Alberto; Martin, Guillaume; Breton, Catherine; Guignon, Valentin; Van Den Houwe, Ines; Mendez, Yaleidis; Sachter-Smith, Gabriel L.; Chase, Rachel; Ruas, Max; Rivallan, Ronan; Paofa, Janet; et al. (Wiley, 2025)
Bananas are nutritious fruits of major importance worldwide. Characterizing their diversity is essential to ensure their conservation and use. A catalog showcasing cultivated bananas genomic diversity was compiled and is to be used as a tool to support the classification of banana cultivars. This research revealed that cultivated banana groups are not all made of identical clones. Materials from recent collecting missions indicated that more banana diversity is expected to be found as the exploration of the banana gene pool continues. These discoveries will drive dynamic conservation strategies for banana genetic resources and should increase their use.Banana is an important food crop cultivated in many tropical and subtropical regions around the world. Because banana cultivars often have low fertility, they are typically propagated clonally, which maintains desirable traits across generations. However, different factors, such as synonymy, incomplete passport data, and environmental effects, complicate the morphological‐based assignment of banana cultivars to specific clones or cultivar groups. In this study, we applied a previously developed genomic‐based tool for fine‐scale characterization of banana ancestry, known as in silico chromosome painting, to high‐throughput genotyping data from 317 banana accessions. This dataset covers most of the globally conserved, studied, and cultivated cultivar groups and includes both genebanks and new, uncharacterized materials. By comparing curated morphological assignation to the genomic patterns resulting from in silico chromosome painting, we compiled a diversity catalog referencing curated passport data, pictures, and chromosome painting patterns of the cultivar groups. Examining the genomic patterns obtained, intra‐cultivar group variability was discovered. In some cultivar groups, mitotic recombination or deletions accumulated clonally. In addition, at least four cultivar groups encompassed cultivars from distinct sexual events co‐existing, notably Pisang Awak with five distinct patterns across two ploidy levels. Finally, additional patterns were discovered in the newest materials of the set, showing that a wider diversity of clones still exists on farm.Banana is an important food crop cultivated in many tropical and subtropical regions around the world. Because banana cultivars often have low fertility, they are typically propagated clonally, which maintains desirable traits across generations. However, different factors, such as synonymy, incomplete passport data, and environmental effects, complicate the morphological‐based assignment of banana cultivars to specific clones or cultivar groups.In this study, we applied a previously developed genomic‐based tool for fine‐scale characterization of banana ancestry, known as in silico chromosome painting, to high‐throughput genotyping data from 317 banana accessions. This dataset covers most of the globally conserved, studied, and cultivated cultivar groups and includes both genebanks and new, uncharacterized materials.By comparing curated morphological assignation to the genomic patterns resulting from in silico chromosome painting, we compiled a diversity catalog referencing curated passport data, pictures, and chromosome painting patterns of the cultivar groups.Examining the genomic patterns obtained, intra‐cultivar group variability was discovered. In some cultivar groups, mitotic recombination or deletions accumulated clonally. In addition, at least four cultivar groups encompassed cultivars from distinct sexual events co‐existing, notably Pisang Awak with five distinct patterns across two ploidy levels. Finally, additional patterns were discovered in the newest materials of the set, showing that a wider diversity of clones still exists on farm.